2005
DOI: 10.1182/blood-2004-03-1204
|View full text |Cite
|
Sign up to set email alerts
|

The hereditary hemochromatosis protein, HFE, lowers intracellular iron levels independently of transferrin receptor 1 in TRVb cells

Abstract: Hereditary hemochromatosis (HH) is an autosomal recessive disease that leads to parenchymal iron accumulation. The most common form of HH is caused by a single amino acid substitution in the HH protein, HFE, but the mechanism by which HFE regulates iron homeostasis is not known. In the absence of transferrin (Tf), HFE interacts with transferrin receptor 1 (TfR1) and the 2 proteins co-internalize, and in vitro studies have shown that HFE and Tf compete for TfR1 binding. IntroductionHereditary hemochromatosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…HFE reduces NTBI uptake in Chinese hamster ovary cells lacking endogenous TfR1 and TBI uptake in Chinese hamster ovary cells transfected with TfR1 (18). A single divalent iron transporter could explain the shared pathway for TBI and NTBI uptake, which functions in the endosome for TBI uptake and on cell membrane for NTBI uptake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HFE reduces NTBI uptake in Chinese hamster ovary cells lacking endogenous TfR1 and TBI uptake in Chinese hamster ovary cells transfected with TfR1 (18). A single divalent iron transporter could explain the shared pathway for TBI and NTBI uptake, which functions in the endosome for TBI uptake and on cell membrane for NTBI uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin is a hormone secreted by the liver that negatively regulates dietary iron uptake by the intestine. HFE can also lower NTBI uptake in isolated primary mouse hepatocytes (9) and in Chinese hamster ovary cells lacking endogenous TfR1 (18). Thus, the mechanism by which HFE regulates iron metabolism still remains elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TfR1 is a type II transmembrane glycoprotein, which contains a large extracellular C-terminal domain (671 amino acids), a single-pass transmembrane domain (28 amino acids), and a short intracellular N-terminal domain (61 amino acids) (3). The tetrapeptide 20 YTRF 23 motif within the cytoplasmic region of TfR1 has been shown as the structural recognition motif to TfR1 endocytosis (4).…”
mentioning
confidence: 99%
“…At physiological concentrations of iron-bound transferrin (10 μM holo-Tf), it was shown that HFE could not compete for binding to TfR1 because of its lower affinity, but that cellular iron levels were reduced by HFE expression. HFE therefore appeared to be regulating some aspect of iron import in the endosome, independent of TfR1 binding (8)(9)(10). HFE may also regulate iron export in some cell types (11,12).…”
mentioning
confidence: 99%